The devil is a part-timer! 18 - Wagahara, Satoshi (Yen Press, 2022)
"Far from the now-familiar comforts of Japan, Emilia carries a heavy heart as Olba forces her to march upon Heavensky Keep. All hope seems lost, but a letter from Ashiya hints that Maou is coming to overturn the situation! Facing each other on the battlefield, the two join together to buy some time and force heaven's carefully written plot off-script...!"--